2019
DOI: 10.1002/adom.201901464
|View full text |Cite
|
Sign up to set email alerts
|

Electrochromic Infrared Light Modulation in Optical Waveguides

Abstract: Electrochromic materials and devices have attracted much attention with their ability to tune the transmissions of visible to infrared (IR) light, allowing the creation of smart windows. This study presents a novel electrochromic device (ECD)‐based photonic device that can modulate IR light intensity in a planar optical waveguide ECD. To configure it, a multilayer ECD made of WO3 is integrated on a polymer optical waveguide platform. By using the waveguide to change the optical properties of the ECD electrical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Despite recent advancements, the search for new functionalized synaptic devices capable of reading electrical synaptic stimulation in an optical manner remains a subject of rigorous research for constructing photonic neuromorphic systems. Of many photonic materials, electrochromic materials have been exploited recently to extend their applications in divergent electronic and photonic technologies beyond their original contributions to smart windows. , Electrolyte-gated three-terminal transistors using WO 3 , SrFeO 2.5 , or VO 2 recently have attracted attention due to their capability of being integrated on an optical waveguide platform and almost exactly emulating the working principle and functions of the biological synapse. Recently, we demonstrated that an electrochromic material can regulate infrared light intensity in a planar optical waveguide and confirmed that a new approach to consider electrochromic materials on a waveguide could pave the way for the development of planar chip-type photonic neuromorphic systems. Herein, we design a waveguide-integrated electrochromic optical synaptic device by applying a poly­(vinyl acetal)-based electrolyte and a WO 3 –NiO complementary structure to reduce the self-erasing phenomenon and further sustain a certain colored state.…”
Section: Introductionmentioning
confidence: 54%
“…Despite recent advancements, the search for new functionalized synaptic devices capable of reading electrical synaptic stimulation in an optical manner remains a subject of rigorous research for constructing photonic neuromorphic systems. Of many photonic materials, electrochromic materials have been exploited recently to extend their applications in divergent electronic and photonic technologies beyond their original contributions to smart windows. , Electrolyte-gated three-terminal transistors using WO 3 , SrFeO 2.5 , or VO 2 recently have attracted attention due to their capability of being integrated on an optical waveguide platform and almost exactly emulating the working principle and functions of the biological synapse. Recently, we demonstrated that an electrochromic material can regulate infrared light intensity in a planar optical waveguide and confirmed that a new approach to consider electrochromic materials on a waveguide could pave the way for the development of planar chip-type photonic neuromorphic systems. Herein, we design a waveguide-integrated electrochromic optical synaptic device by applying a poly­(vinyl acetal)-based electrolyte and a WO 3 –NiO complementary structure to reduce the self-erasing phenomenon and further sustain a certain colored state.…”
Section: Introductionmentioning
confidence: 54%
“…As such, a small amount of Li + ion intercalation/deintercalation in the WO 3 active electrochromic layer alters the plasmon’s mode coupling condition significantly. The achieved modulation depth per volt (8 dB/V) in the plasmochromic modulator (10 μm long) is an order of magnitude higher than that of other state-of-the-art voltage-driven plasmonic electrooptic modulators. ,, Since the modulation depth greatly depends on the length of the plasmochromic waveguide, we further show through simulation that, in principle, the modulation depth could be further enhanced to exceed 50 dB by using longer (>20 um) waveguides, while operating at much lower voltages. Considering recent advances in nanofabrication technology and nanoscale solid-state electrochromic materials, such a plasmochromic platform could potentially pave the way toward novel applications in low power consumption nanoplasmonic circuits and computing.…”
mentioning
confidence: 82%
“…23−26 Merging nanoplasmonics with EC materials provides new avenues in dynamically controlling nanoplasmonic devices. Such an intriguing plasmochromic (PC) platform offers novel functionalities, such as dynamic light control switching, 1,27 structural color generation, 23,24,28 and metasurface tunability at a low power consumption.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[ 36 ] Cathodic ECMs include WO 3 , MoO 3 , Nb 2 O 5 , TiO 2, Ta 2 O 5, and their derivatives or mixtures. [ 37–39 ] Meanwhile, various materials including NiO, IrO 2 , V 2 O 5 , and Prussian blue analogs, etc., are usually chosen as anodic ECMs. [ 40–43 ] A typical electrochromic device usually consists of two transparent conductive layers, an electrochromic layer, an ion transport layer (electrolyte), and an ion storage layer.…”
Section: Introductionmentioning
confidence: 99%